Hubungan Pengetahuan Ibu terhadap Pemberian Imunisasi BCG Tepat Waktu di Wilayah Kerja Puskesmas Muara Fajar Kota Pekanbaru - Rahmi Isrohati; Rifa Yanti; Rizka Mardiya; Meirita Herawati (Pusat riset dan Inovasi Nasional, 2026)
Bacillus Calmette–Guérin (BCG) immunization is a mandatory basic immunization that must be administered to infants before two months of age as a preventive measure against tuberculosis. Timely administration of the BCG vaccine is crucial to ensure optimal protection and to maintain continuity of subsequent immunization schedules. Maternal knowledge is one of the factors influencing the timeliness of immunization. The achievement of BCG immunization at Muara Fajar Community Health Center in 2025 was 76.1%, still below the annual target of 90%. This study aimed to determine the relationship between maternal knowledge and the timely administration of BCG immunization among infants aged 0–2 months in the working area of Muara Fajar Public Health Center, Pekanbaru City. This study employed a quantitative method with a cross-sectional design. A total of 59 mothers with infants aged 0–6 months were selected using accidental sampling. Data were collected through questionnaires assessing maternal knowledge of BCG immunization and the timeliness of BCG vaccine administration. Data analysis was conducted using the Chi-square test with a significance level of p<0.05. The results showed that most mothers were aged 26–35 years (59.3%), had a senior high school education (52.2%), and were housewives (71.2%). Nearly half of the respondents had low knowledge levels (47.5%), while 54.2% of infants received BCG immunization on time. The Chi-square test revealed a significant association between maternal knowledge and timely BCG immunization (p=0.001). This study concludes that maternal knowledge plays a crucial role in ensuring timely BCG immunization in infants.